Un mouvement gai dans la lutte contre le sida : les soeurs de la perpétuelle indulgence - Welzer-Lang, Daniel; Le Talec, Jean-Yves; Tomolillo, Sylvie (Paris : L'Harmattan, 2000)
Fonds Suzan Daniel (FSD)
Frans
Monografie